2020
DOI: 10.1371/journal.pone.0227991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sequence variability hotspots in Cranichideae plastomes (Orchidaceae, Orchidoideae)

Abstract: This study reports complete plastome sequences for six species of Neotropical Cranichideae and focuses on identification of the most variable regions (hotspots) in this group of orchids. These structure of these six plastomes is relatively conserved, exhibiting lengths ranging between 142,599 to 154,562 bp with 36.7% GC on average and exhibiting typical quadripartite arrangement (LSC, SSC and two IRs). Variation detected in the LSC/IR and SSC/IR junctions is explained by the loss of ndhF and ycf1 length variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 61 publications
5
19
0
1
Order By: Relevance
“…Molecular markers relative to these regions serve for the identification of valuable herbal medicinal plants (Cho et al, 2015;Hong et al, 2017;Park et al, 2018a,b). In terms of nucleotide diversity, most divergent regions were non-coding, which is again consistent with other cp genomes (Schroeder et al, 2016;Zhitao et al, 2017;Liu E. et al, 2019;Smidt et al, 2020). Other cp genomes were reported to have highly variable non-coding regions at trnS-GCU-trnG-UCC, trnC-GCA-petN, psaA-ycf3, trnI-CAU-ycf2, psbE-petL, and rps15-ycf1.…”
Section: Characterization Of Cp Genome and Genetic Variations In Arnesupporting
confidence: 85%
“…Molecular markers relative to these regions serve for the identification of valuable herbal medicinal plants (Cho et al, 2015;Hong et al, 2017;Park et al, 2018a,b). In terms of nucleotide diversity, most divergent regions were non-coding, which is again consistent with other cp genomes (Schroeder et al, 2016;Zhitao et al, 2017;Liu E. et al, 2019;Smidt et al, 2020). Other cp genomes were reported to have highly variable non-coding regions at trnS-GCU-trnG-UCC, trnC-GCA-petN, psaA-ycf3, trnI-CAU-ycf2, psbE-petL, and rps15-ycf1.…”
Section: Characterization Of Cp Genome and Genetic Variations In Arnesupporting
confidence: 85%
“…A full reading frame for ndhG was observed only in B. exaltatum . Loss of ndh genes has been previously reported in orchids ( Chang et al, 2006 ; Yang et al, 2013 ; Luo et al, 2014 ; Kim et al, 2015 ; Zhitao et al, 2017 ; Kim and Chase, 2017 ; Mauad et al, 2019 ; Smidt et al, 2020 ) and is useful in comparative analyses but not in phylogenetics owing to high levels of homoplasy depicted by the independent loss of some ndh genes in a number of species of Orchidaceae ( Kim et al, 2015 ; Kim and Chase, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, numerous orchid plastid genomes have been sequenced. As a result, various plastid markers have been proposed for Orchidaceae ( Yang et al, 2013 ; Niu et al, 2017a , c ; Zhitao et al, 2017 ; Dong et al, 2018 ; Zhu et al, 2018 ; Li et al, 2019 ; Smidt et al, 2020 ). For instance, Niu et al (2017c) suggested that trnK-rps16 , trnS-trnG , and rps16-trnQ IGSs could be used for genera within Epidendroideae, and clpP-psbB and rps16-trnQ for Cypripedioideae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations